Łódzka zieleń w cieniu Wielkiej Wojny - Stawiszyńska, Aneta (Acta Universitatis Lodziensis. Folia Historica, 2014)
The outbreak of the First World War was connected with occurrence of significant economic problems in the city. In connection with lack of combustible materials, large scale deforestations of parks and forests located around the city took place. In later years, the remaining tree stands were protected better due to introduction of many preventive measures. New parks were created and existing green areas were modernized. During the War, the green areas located in the city were also improved, especially by executing numerous plantation-related undertakings. Offices responsible for maintaining green areas were also caring about military cemeteries. Even though the significant attempts were carried out, Łódź recorded tremendous financial losses due to the devastation of forests located around the city.